IMPLICATIONS OF COMPANY FINANCIAL PERFORMANCE AND INDEPENDENT AUDITOR REPUTATION ON AUDIT DELAY - Prasetiyo, Yudhi; Wisnantiasri, Sila Ninin; Riyani, Etik Ipda (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
The proper submission of financial reports affects the company's reputation because it ensures that short-term and long-term decisions and policies are made quickly so that the public gets information quickly. This study aims to determine whether audit delays are influenced by financial performance and examiner reputation. The period 2016-2021 is the time span of this research with various types of industrial or business companies listed on the Indonesia Stock Exchange. This study is quantitative in nature. The test sample consists of 126 entities and is taken by purposive sampling. The data analysis technique uses multiple linear regression. Based on the results of the analysis obtained, it was found that liquidity proxied in the quick ratio did not show significant results on audit delay, then profitability proxied by net profit margin showed significant results on audit delay, then for solvency proxied by debt to assets gave results had no significant effect on audit delay, then for external auditor reputation also did not show significant results on audit delay.